2010
DOI: 10.1111/j.1751-7893.2010.00163.x
|View full text |Cite
|
Sign up to set email alerts
|

Early intervention with second‐generation antipsychotics in first‐episode psychosis: results of an 8‐week naturalistic study

Abstract: Early intervention with low doses of four SGAs led to rapid symptom reduction in first-episode psychotic patients with severe psychopathology. Although no clear medication advantages were observed in the short term, longer duration studies with larger samples will be required for determining efficacy, rates of compliance, relapse prevention and diminished incidence of extrapyramidal signs and symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…The total number of patients in these studies was 4139 (2594 male, 1545 female). Five studies were double blinded, [32][33][34][35][36] one was single blinded, 37 and 22 were open label. 20,24,31,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] Of these 28 studies, 12 (42.8%) were funded by pharmaceutical companies, 6 (21.4%) were funded by institutional or government agencies, and 3 (10.7%) were funded by pharmaceutical companies and institutional agencies.…”
Section: Resultsmentioning
confidence: 99%
“…The total number of patients in these studies was 4139 (2594 male, 1545 female). Five studies were double blinded, [32][33][34][35][36] one was single blinded, 37 and 22 were open label. 20,24,31,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] Of these 28 studies, 12 (42.8%) were funded by pharmaceutical companies, 6 (21.4%) were funded by institutional or government agencies, and 3 (10.7%) were funded by pharmaceutical companies and institutional agencies.…”
Section: Resultsmentioning
confidence: 99%
“…For the short-term meta-analysis, 39 weight change outcomes were extracted from 21 unique intervention studies 20,31-35,37-47,51-54 and 23 BMI change outcomes from 11 unique samples. 20,33,37,41,42,44,[51][52][53][54][55] Nine of these studies lasted less than 12 weeks. 32,37,[39][40][41][45][46][47]52 Weight change From analysis of the selected studies, the overall mean weight gain difference between AP medications and placebo was 3.22 kg (CI = 1.65-4.80, P < 0.001).…”
Section: Short-term Results (≤12 Weeks)mentioning
confidence: 99%
“…For instance, it would be important to identify people at high risk or in the early stages of psychosis, given that preliminary data have suggested that low doses of atypical antipsychotics associated with psychosocial interventions may delay the onset of psychosis in some individuals [63], and that early treatment with atypical antipsychotics may reduce the risk of transition to psychosis [64]. In addition, psychosocial interventions such as cognitive behavioral therapy and family interventions as well as close monitoring may be safer, more acceptable and more effective for at least a subgroup of patients in the early stages of psychosis [65], whereas patients with severe psychopathology at onset may benefit from an early intervention with low doses of second-generation antipsychotics [66]. The role of psychotherapy in its different forms should be better investigated in relation to DUP/DUI, in order to detect potential differences in efficacy between medications and psychotherapy or even against combined treatments.…”
Section: Resultsmentioning
confidence: 99%